Adaptation of Counseling Services to Social Media Challenges Among Adolescen - Wenda Asmita; Mita Rahmi; Ghina Raudhatul Jannah; Dita Widya Putri; Reza Firmansyah (Program Studi Bimbingan Konseling, Fakultas Tarbiyah dan Ilmu Keguruan UIN Bukittinggi, 2025)
This study examines the adaptation of counseling services in response to the psychological challenges adolescents face in increasingly digital social environments. Through a qualitative descriptive literature review, the research analyzes emerging counseling approaches specifically designed to address social media-related issues among adolescents aged 12-19 years. The methodology involved systematic analysis of 43 selected publications from 2015-2024, incorporating both Indonesian and international perspectives to ensure cultural relevance. Results identify several significant adaptations in counseling practices, including: (1) specialized therapeutic frameworks such as Digital-enhanced Cognitive Behavioral Therapy and Mindfulness-based Digital Awareness Therapy that directly address digital-specific psychological mechanisms; (2) technological transformations in counseling delivery through online platforms and chat-based interventions that increase accessibility and engagement; (3) integration of digital literacy components within counseling interventions to enhance adolescents' critical understanding of platform mechanics and media influences; (4) culturally responsive adaptations that align interventions with local values while addressing universal psychological impacts; (5) preventive approaches implemented in school and community settings before psychological distress manifests; and (6) family-based interventions that improve parental understanding of adolescent digital experiences. The findings demonstrate that effective counseling adaptations extend beyond superficial adjustments to fundamental reconsiderations of counseling theories, techniques, delivery methods, and ecological approaches. This research contributes to the development of more responsive counseling interventions for digitally connected adolescents and highlights the importance of continuous adaptation as digital technologies evolve.